A case report demonstrating intestinal tuberculosis in an infra-umbilical incisional hernia - Tarique, M.; Aziz, Iqbal (International Journal of Research in Medical Sciences, 2023)
Abdominal tuberculosis is common but it is rare to diagnose it through the contents of hernia. Clinical presentations of abdominal tuberculosis are diverse depending on the organ involved in the abdominal cavity. Thirty-five-year-old female was admitted in the surgical ward of Ajmal khan Tibbiya college hospital, Aligarh Muslim university Aligarh with the complaints of a swelling in the infra-umbilical region in a previous vertical LSCS incision. Hernia repair surgery revealed the features of intestinal tuberculosis which was confirmed by histopathology. Anti-tuberculosis treatment was started and she was in a stable condition upon discharge. This case report is the first documented case of intestinal tuberculosis in an infra-umbilical incisional hernia. The case report highlights the relevance of advance investigations in simple looking hernial cases. There is very limited data within literature related to the histopathological diagnosis of hernial sacs in an endemic area of tuberculosis, but it will be beneficial for surgeons working in endemic areas of tuberculosis.